Anna Espelt - Troyano Puig, Ruth (Wine Portraits, 2016)
Retrats de Vi (Wine Portraits), focuses on several oenologists, all trained at the URV, who use their professional and personal experience to explain what their work consists of, their objectives and the challenges they face. But, above all, they show us their love of a profession that has deep roots in our land.